2010
DOI: 10.1086/655901
|View full text |Cite
|
Sign up to set email alerts
|

Are Host Genetics the Predominant Determinant of Persistent NasalStaphylococcus aureusCarriage in Humans?

Abstract: Host genetic factors appeared to be the predominant determinant for S. aureus persistent nasal carriage in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
109
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 49 publications
6
109
1
1
Order By: Relevance
“…The volunteers enrolled in the study were healthy adult Wayampi Amerindians from the village of Trois-Sauts, in French Guyana, where huts with no modern facilities are disseminated over ϳ3 km along the Oyapok river. Their living conditions and microbiological follow-up since 2001 has been extensively described elsewhere (9)(10)(11)(12)(13). This is a genetically homogenous population of ϳ500 inhabitants, still living mostly in a traditional manner, including alimentation, which is provided by hunting, fishing, and raising crops.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The volunteers enrolled in the study were healthy adult Wayampi Amerindians from the village of Trois-Sauts, in French Guyana, where huts with no modern facilities are disseminated over ϳ3 km along the Oyapok river. Their living conditions and microbiological follow-up since 2001 has been extensively described elsewhere (9)(10)(11)(12)(13). This is a genetically homogenous population of ϳ500 inhabitants, still living mostly in a traditional manner, including alimentation, which is provided by hunting, fishing, and raising crops.…”
Section: Methodsmentioning
confidence: 99%
“…However, a resident paramedic ensures fully free access to allopathic medicine and records all health care deliveries, including antibiotics. During the last sampling campaign, which took place in October 2010, we tested 151 individuals for E-ESBL intestinal carriage, as described previously (9,11,13). In addition, a fecal sample of about 5 g that had recently passed (less than 2 h earlier) was diluted 1:10 in RNAlater (Applied Biosystems, Villebon-sur-Yvette, France), thoroughly mixed, and immediately frozen at Ϫ20°C before being taken to the laboratory, without defrosting, and stored at Ϫ80°C until harvesting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is clear that host genetics, immune responses, and strain differences contribute (12)(13)(14)(15)(16)(17), there are likely other important factors. As the anterior nares appear to be a critical S. aureus reservoir (1,18,19) and because antecedent nasal carriage increases the risk for infection (1,20,21), a better understanding of nasal microbial ecology may yield valuable clues regarding SSTI susceptibility.…”
mentioning
confidence: 99%
“…In addition, patients colonized with Esp-secreting S. epidermidis correlated with absence of S. aureus in the nasal cavity (7). One study observed that single nucleotide polymorphisms (SNPs) in C-reactive protein and interleukin 4 (IL-4) genes correlated with S. aureus nasal colonization (8), whereas another found a correlation with SNPs in the glucocorticoid receptor gene (9).…”
mentioning
confidence: 99%